Correlation of capecitabine-induced skin toxicity with treatment efficacy in patients with metastatic colorectal cancer: results from the German AIO KRK-0104 trial - Stintzing, S (Nature Publishing Group, 2011)
BACKGROUND: The AIO KRK-0104 randomised phase II trial investigated the efficacy and safety of two capecitabine-based regimens: combination of capecitabine and irinotecan (CAPIRI) plus cetuximab (CAPIRI-C) and combination of capecitabine with oxaliplatin (CAPOX) plus cetuximab (CAPOX-C) in the first-line treatment of metastatic colorectal cancer (mCRC). Treatment-related skin toxicity (ST) was evaluated separately for capecitabine and cetuximab. The present analysis investigates the correlation of capecitabine-attributed ST (Cape-ST) and parameters of treatment efficacy. METHODS: Patients with mCRC were randomised to cetuximab (400 mg m(−2), day 1, followed by 250 mg m(−2) weekly) plus CAPIRI (irinotecan 200 mg m(−2), day 1; capecitabine 800 mg m(−2), twice daily, days 1–14, every 3 weeks), or cetuximab plus CAPOX (oxaliplatin 130 mg m(−2), day 1; capecitabine 1000 mg m(−2), twice daily, days 1–14, every 3 weeks). RESULTS: Of 185 recruited patients, 149 (CAPIRI-C, n=78; CAPOX-C, n=71) received study treatment beyond the first tumour assessment and were evaluable for efficacy. Capecitabine-attributed ST, predominantly hand–foot syndrome, was observed in 32.2% of patients. Capecitabine-attributed ST grade 1–3 was associated with a significantly higher disease control rate (DCR) (97.9 vs 86.1%, P=0.038) compared with grade 0 toxicity. Moreover, Cape-ST grade 1–3 related to a markedly longer progression-free survival (PFS) (9.9 vs 5.6 months, P<0.001) and overall survival (OS) (32.8 vs 22.4 months, P=0.008). Separate analyses of treatment arms indicated that the effect of Cape-ST on PFS remained significant for both arms, whereas the effect on OS remained apparent as a strong trend. CONCLUSION: This analysis supports the hypothesis that for the evaluated regimens, a correlation exists between Cape-ST and treatment efficacy regarding DCR, PFS, and OS.